2016
DOI: 10.1038/srep28597
|View full text |Cite
|
Sign up to set email alerts
|

Metformin is a novel suppressor for transforming growth factor (TGF)-β1

Abstract: Metformin is a widely used first-line antidiabetic drug that has been shown to protect against a variety of specific diseases in addition to diabetes, including cardiovascular disorders, polycystic ovary syndrome, and cancer. However, the precise mechanisms underlying the diverse therapeutic effects of metformin remain elusive. Here, we report that transforming growth factor-β1 (TGF-β1), which is involved in the pathogenesis of numerous diseases, is a novel target of metformin. Using a surface plasmon resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 26 publications
6
70
0
Order By: Relevance
“…There are two possibilities for the AMPKα2‐independent effects, AMPK‐independent effects and AMPKα1‐dependent effects. Indeed, several other studies have reported that metformin acts via AMPK‐independent pathways . In our previous study, which used Compound C (an AMPK inhibitor) and a dominant‐negative adenovirus to inhibit AMPK activity, we found that metformin nonetheless inhibits TGFβ1‐induced collagen synthesis in cardiac fibroblasts .…”
Section: Discussionmentioning
confidence: 65%
“…There are two possibilities for the AMPKα2‐independent effects, AMPK‐independent effects and AMPKα1‐dependent effects. Indeed, several other studies have reported that metformin acts via AMPK‐independent pathways . In our previous study, which used Compound C (an AMPK inhibitor) and a dominant‐negative adenovirus to inhibit AMPK activity, we found that metformin nonetheless inhibits TGFβ1‐induced collagen synthesis in cardiac fibroblasts .…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies indicated that metformin was a novel TGF-β suppressor with therapeutic potential for numerous diseases [33]. In our study, we used TGF-β1 to induce EMT and explore the possible mechanism of metformin that inhibited TGF-β1-induced EMT in cervical cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Metformin was also identified as a novel TGFβ1 suppressor [16]. VEGF has been shown to play a vital role in the regulation of physiological and pathological angiogenesis [17].…”
Section: Western Blot Represents One Of Three Independent Experimentsmentioning
confidence: 99%